An averaging scheme for the efficient approximation of time-periodic flow problems. (15th January 2021) - Richter, Thomas
Highlights: Acceleration scheme for the quick identification of cyclic limit states for flow problems. Forward method that does not require adjoint problems. Simple analysis for the Stokes problem. Numerical examples show efficiency for Navier-Stokes. Abstract: We study periodic solutions to the Navier-Stokes equations. The transition phase of a dynamic Navier-Stokes solution to the periodic-in-time state can be excessively long and it depends on parameters like the domain size and the viscosity. Several methods for an accelerated identification of the correct initial data that will yield the periodic state exist. They are mostly based on space-time frameworks for directly computing the periodic state or on optimization schemes or shooting methods for quickly finding the correct initial data that yields the periodic solution. They all have a large computational overhead in common. Here we describe and analyze a simple averaging scheme that comes at negligible additional cost. We numerically demonstrate the efficiency and robustness of the scheme for several test-cases and we will theoretically show convergence for the linear Stokes problem.